2023
DOI: 10.1186/s12950-023-00344-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in acute coronary syndrome

Abstract: Acute coronary syndrome (ACS) is a group of clinical syndromes caused by acute myocardial ischemia, which can cause heart failure, arrhythmia and even sudden death. It is the major cause of disability and death worldwide. Neutrophil extracellular traps (NETs) are reticular structures released by neutrophils activation and have various biological functions. NETs are closely related to the occurrence and development of ACS and also the subsequent damage after myocardial infarction. The mechanisms are complex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…NETs are reticular structures released by neutrophil activation and are closely related to the subsequent damage after MI. 17 NETs are involved in the inflammatory pathophysiology of a variety of illnesses, such as cardiovascular and infectious diseases. 25 PMA can induce neutrophil aggregation and subsequent NETs release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NETs are reticular structures released by neutrophil activation and are closely related to the subsequent damage after MI. 17 NETs are involved in the inflammatory pathophysiology of a variety of illnesses, such as cardiovascular and infectious diseases. 25 PMA can induce neutrophil aggregation and subsequent NETs release.…”
Section: Resultsmentioning
confidence: 99%
“… 16 For example, one study found that in addition to providing a scaffold for thrombus formation, NETs formation also exacerbates endothelial cell injury, which may be an important contributor to the development of MI. 17 …”
Section: Introductionmentioning
confidence: 99%
“…During NETosis, autoantigens, proin ammatory mediators, proteases, and cytotoxic enzymes are exposed, leading to cytokine storm [50]. Recent studies have highlighted that neutrophil-induced NETs are central to the development of cytokine storm and immunopathological complications such as deep vein thrombosis, myocardial infarction, and thrombotic microangiopathy [51][52][53]. Interactions between activated neutrophils, platelets, and coagulation cascade are important in the process of thrombosis in COVID-19 [54].…”
Section: Discussionmentioning
confidence: 99%
“…The various pathomechanisms of NETs in atherosclerosis and thrombosis may also contribute to the development of MI [52,53]. Furthermore, granular proteins (NET components) can recruit monocytes to the culprit site by triggering monocyte chemoattractant protein 1 release from local ECs [54].…”
Section: Nets In Cardiovascular Diseasesmentioning
confidence: 99%